Factors Associated with Ownership of Acceptance Health Certificate And Consumer Satisfaction of Refill Drinking Water Depot in Kuantan Singingi District. - Eliza Fitria; Zulkarnaini Zulkarnaini; M. Yulis Hamidy (Program Pascasarjana Universitas Riau, 2017)
This study was in November 2016 to January 2017 located in Kuantan Singingi. The purpose of this study is to analyze the relationship simultaneously or partially and the influence of direct and indirect between the knowledge of the owner of the depot, training owners depot, supervision of health professionals and the bacteria total coliform depot refill drinking water to the ownership of acceptance healthy certificate in Kuantan Singingi and analyze the relationship healthy acceptance certificate of ownership to consumer satisfaction in drinking water refill depot in Kuantan Singingi. Based on the results of research, knowledge variable depot owners of drinking water, training, supervision and inspection of health workers total coliform bacteria simultaneously affect the ownership of acceptance healthy certificate drinking water refill depot in Kuantan Singingi amounted to 58.4%. Partially no influence between total coliform bacteria examination depot drinking water on a healthy acceptance certificate of ownership which is indicated by p value of 0.475. While variable knowledge, training, supervision of health workers significantly affect ownership of acceptance healthy certificate of with p value respectively by 0.02, 0.09 and 0.00. Influence direct of knowledge on ownership healthy acceptance certificate of 1.2% and indirectly through training and supervision respectively by 0.4% and 1.8% and the total effect of 3.4%. Effect of training on healthy acceptance certificate direct ownership of 6.8% and indirectly through knowledge and supervision by 0.4% and 8.3% and the total effect of 15.5%. Effect of supervision of the ownership certificate of acceptance healthy 32.2% directly and indirectly through knowledge and training of respectively 1.8% and 4.3% and the total effect of 38.3%. Ownership certificates are eligible to healthy drinking water refill depot does not affect customer satisfaction in Kuantan Singingi with p value of 3.12 and a value of R square 0.15.